2009
DOI: 10.1111/j.1745-4603.2009.00185.x
|View full text |Cite
|
Sign up to set email alerts
|

White Guava Fruit and Purees: Textural and Rheological Properties and Effect of the Temperature

Abstract: ABSTRACTj ts_185 334..345 This study focuses on the effect of temperature on the rheological properties of white guava puree. The results of the textural analysis on the whole guava as well as the rheological analysis on the puree made from it showed different behaviors depending on whether the fruit was unripened or ripened. A relationship was observed between the textural properties of the whole guava and the rheological parameters of its puree. The behavior of white guava puree was thixotropic and pseudo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…According to the literature, shear thinning behavior is very common in different fruit pulps. The Power-Law model was used to describe the flow behavior of other fruit pulps and purees, such as capuaçu (Theobroma grandiflorum) [34], guava [35], and blackberry [19]. However, in contrast to the present work, most studies point out that fruit pulps present a yield stress, as in the case of mango [20], blueberry [18], siriguela (Spondias purpurea L.) [16], and umbu (Spondias tuberosa) [36] pulps.…”
Section: Rheological Behaviormentioning
confidence: 76%
“…According to the literature, shear thinning behavior is very common in different fruit pulps. The Power-Law model was used to describe the flow behavior of other fruit pulps and purees, such as capuaçu (Theobroma grandiflorum) [34], guava [35], and blackberry [19]. However, in contrast to the present work, most studies point out that fruit pulps present a yield stress, as in the case of mango [20], blueberry [18], siriguela (Spondias purpurea L.) [16], and umbu (Spondias tuberosa) [36] pulps.…”
Section: Rheological Behaviormentioning
confidence: 76%
“…The rheological properties of fluid foods are affected by temperature, concentration of solute, its molecular weight, pressure, suspended matter and level of additives (Bourne 2002). The relationship between shear stress and shear rate was described by Ostwald-DeWaele model or power law equation (Sanchez et al 2009;Sogi et al 2010)…”
Section: Introductionmentioning
confidence: 99%
“…According to Chin et al (2009) and Sánchez et al (2009), pummelo juice concentrate and white guava puree showed behavior index (n) values below unity at temperatures from 6 to 75 °C and 10 to 60 °C, respectively, indicating pseudoplastic behavior. Saravacos and Maroulis (2001) showed that the values for the behavior index (n) for fruit purees were generally in the range from 0.30 to 0.50.…”
Section: Rheological Behavior Of Brazilian Cherry Pulpmentioning
confidence: 99%